2013
DOI: 10.1080/03235408.2013.765136
|View full text |Cite
|
Sign up to set email alerts
|

Protection of cowpea,Vigna unguiculataL. (Walp.) withNewbouldia laevis(Seem.) extracts against infestation byCallosobruchus maculatus(Fabricius)

Abstract: Evaluation of protectant ability of Newbouldia laevis (Seem.) extracts against infestation by Callosobruchus maculatus in cowpea, Vigna unguiculata L. (Walp.) was carried out in the laboratory at ambient temperature of 28 ± 2°C and 70 ± 5% relative humidity. Extracts from wood ash, leaf, stem and root bark were tested at different concentrations of 0, 1, 2, 3, 4 and 5%. One hundred per cent mortality of adult beetles was achieved at all concentrations within 72 h of treatment with extracts except in wood ash a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 10 publications
5
17
0
Order By: Relevance
“…Also, the high mortality recorded could due to inability of the insect to feed on the seeds that have been coated with the fractions of the oil, thus leading to the starvation of the insect. The result obtained agreed with the findings of Ashamo et al (2013) and Oni (2014) in which extracts of botanicals have been found to cause mortality of C. maculatus. …”
Section: Discussionsupporting
confidence: 91%
“…Also, the high mortality recorded could due to inability of the insect to feed on the seeds that have been coated with the fractions of the oil, thus leading to the starvation of the insect. The result obtained agreed with the findings of Ashamo et al (2013) and Oni (2014) in which extracts of botanicals have been found to cause mortality of C. maculatus. …”
Section: Discussionsupporting
confidence: 91%
“…As soon as they were in contact with the kaolin powder, these respiratory openings were blocked thus causing the asphyxiation and the insects' mortality. Don-Pedro (1989), Ileke and Olotuah (2012), Ashamo et al (2013), andAL-Dabbagh (1993) showed that the most significant characteristic of an inert dust was its great capacity for absorption of water and the lipids. Thus the kaolin powder applied absorbed water and the lipids coming from the insect hardened body, causing its death.…”
Section: Discussionmentioning
confidence: 99%
“…Many diseases, fungi, bacteria and even insects and other pests have developed resistances to many popular synthetic drugs and pesticides [5,6]. For example, many malaria drugs are no longer effective as before Basco and Ringwald [5].…”
Section: Introductionmentioning
confidence: 99%